Community capitals, agricultural productivity, and household well-being in smallholder sugarcane systems - Martínez-Moyano, Edgar; Bermeo-Sandoval, Brian; Buenaventura-Arturo, Alejandro; Gutiérrez-Rojas, Yojan; Muñoz-Ramirez, Herminton; Sánchez-Rojas, Ivan Camilo; Rojas-Peña, Oscar Raúl (Revista de Ciencias Agrícolas, 2025)
The cultivation of sugarcane (Saccharum spp.) for panela production is a key livelihood source for rural households in Colombia, particularly in the southwestern region of the country. Understanding the subsistence strategies associated with this activity and their connection to rural well-being is essential for promoting sustainable productive development. This study examine the influence of community capitals on the well-being of 92 panela-producing households, categorized into three livelihood typologies: (i) diversified, (ii) innovative, and (iii) traditional. Correlations between these typologies and various forms of community capital, human, social, built, natural, financial, political, and cultural, were assessed to identify shared patterns in livelihoods. Diversified households (55.9%) engage in multiple economic activities, including coffee, avocado, and sugarcane cultivation, along with livestock and pig farming. Innovative households (28.3%) primarily depend on sugarcane cultivation, whereas traditional households (11.9%) exhibit low productivity and rely predominantly on coffee as their main income source. The findings revealed that differentiated access to and management of community capitals significantly affect household well-being, with integrated and diversified strategies yielding better outcomes. Furthermore, strengthening skills, knowledge, and networking capacities is crucial for enhancing the social appropriation of sugarcane-related knowledge. This, in turn, can guide more effective strategies for the development of the panela sector and contribute to the overall well-being of rural farming households.